Pendampingan dan Evaluasi Pelaksanaan Kurban di Desa Kedung Umpal, Kecamatan Cibinong, Kabupaten Bogor pada Masa Pandemi Covid-19 - Tetty Barunawati Siagian; Gary Yefta Herbeth Siagian (Institut Pertanian Bogor, 2023)
The purpose of this community service is to provide assistance in the slaughtering and handling of sacrificial animals during the Implementation of Emergency Restrictions on Community Activities (PPKM) against Ministry of Religion regulation No 17 of 2021. This community service uses a qualitative descriptive method obtained from observations, questionnaires and interviews with qurban officers in Kedung Umpal Village, Cibinong Sub District, Bogor Districts, West Java Province The results showed that the slaughter and handling of sacrificial animals in the village of Kedung Umpal Cibinong did not follow the rules issued by the ministry of religion No. 17 of 2021 regarding the procedures for slaughtering sacrificial animals during the emergency PPKM period, including the application of social distancing, health protocols and cleanliness of sacrificial officers and hygiene. tool. Based on these results, it can be concluded that the awareness of the officers handling and slaughtering sacrificial animals during the emergency PPKM period was still not aware of the rules set by the government.